2023
DOI: 10.1371/journal.pone.0286005
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal evolution of acoustic emission events and initiation of stress fields in the fracturing of rock mass around a roadway under cyclic high-stress loading

Gang Lei,
Dawei Wu,
Shengyan Zhu

Abstract: To study fracture mechanisms and initiation of stress fields in the rock mass around a roadway subjected to cyclic stress, a series of loading and unloading tests were conducted on the rock mass around the roadway by using high-precision acoustic emission (AE) monitoring. The results show that intense AE activities occur in a specimen during cyclic load-holding at different levels. With the increase in the number of cycles, the overall stability of the specimen gradually decreases. In the cyclic loading and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Zhao et al [ 19 ] obtained AE parameters and typical modes for different fracture types, discussing the energy release characteristics of each fracture mechanism. Lei et al [ 20 ] through a series of loading and unloading experiments on surrounding rocks, found that the spatial distribution of AE events is related to the stress state and structure of the specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [ 19 ] obtained AE parameters and typical modes for different fracture types, discussing the energy release characteristics of each fracture mechanism. Lei et al [ 20 ] through a series of loading and unloading experiments on surrounding rocks, found that the spatial distribution of AE events is related to the stress state and structure of the specimens.…”
Section: Introductionmentioning
confidence: 99%